A computationally reduced version of the fast H∞ filter. (June 2018) - Nishiyama, Kiyoshi
Abstract: The fast H ∞ filter is designed to overcome the performance limitations of the fast Kalman filter and the fast transversal filter used for system identification; however, its computational complexity exceeds O ( 7 N ), the complexity of the original fast transversal filter. In this work, a computationally reduced version of the fast H ∞ filter is derived as an a posteriori error formulation of the fast H ∞ filter using a conversion factor. The conversion factor-based fast H ∞ filter provides the same performance as the fast H ∞ filter at the expense of a computational cost comparable to that of the fast transversal filter.